Correction: Hematopoietic stem cell transplantation for children with acute myeloid leukemia - results of the AML SCT-BFM 2007 trial - Sauer, Martin Günther; Greil, Johann (Leukemia, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.